Penduduk Semban di Atas Angin Bergotong Royong Mengetam Padi (The Sembans’ Villagers, The Village Above the Cloud, Collaborate in a Communal Effort to Harvest Rice During the Harvesting Season.) - Hakimi, Halim (UNIMAS Publisher, 2025)
Artist: Hakimi bin Halim Medium: Digital Print With Glitter Laminated Surfaces The work in question is the initial creation within a span of 10 years of its production. It depicts Ring Ladies taking a break from rice threshing during the harvest season, engaging in the act of chewing Sogel (tobacco mixed with betel nut). What captivates the viewer in this photojournalistic piece is the simultaneous placement of something in the mouths of all three subjects, aligning with the photographic concept of Henri Cartier-Bresson known as the Decisive Moment. The Decisive Moment refers to a unique and fleeting instance that occurs only once and will not be repeated.